Bonhoeffer's Eighth Day: The Orders of Preservation and a Theology of Natural Ability. Issue 2 (10th November 2014) - Hickman, Lisa Nichols
<x content-type="archive" xml:space="preserve">Abstract</x> The award-winning Belgian film Le huitième jour, about a young man with Down syndrome, begins with static on a television screen. This reflects the current state of disability study: much has been accomplished through the work of Nancy Eiesland, Amos Yong, and John Swinton, but there still is static in the conversation. Dietrich Bonhoeffer rejected the theological discourse of his day regarding the orders of creation and argued instead for the orders of preservation. This turn, in the area of theology and disability, means a move away from questions about God's creating (or not) of disability, and instead moves toward the preservation of life in Christ. In so doing, Bonhoeffer takes a surprising stance as a Protestant by drawing on natural law theology and points to our high calling in life on "the eighth day."